Efficacy and cardiac safety of aldoxorubicin in metastatic solitary fibrous tumour - Karolina Vosylius; Gareth Price; Andrea Napolitano; Charlotte Benson; Nicos Fotiadis; Khin Thway; Ka Hou Christien Li; Robin L Jones (Rare Tumors)
Solitary fibrous tumours (SFT) are very rare mesenchymal neoplasms. While surgery remains a standard treatment for localised disease, effective and long term treatment options for metastatic disease are lacking, making the use of aldoxorubicin a novel and promising systemic treatment in SFTs. We present a 30-year-old male who underwent surgical resection for a solitary fibrous tumour of the right leg. Postoperative imaging revealed metastatic disease in the liver and left upper quadrant. He was initially treated with pazopanib but experienced disease progression after 24 weeks. The patient was then enrolled on a phase III trial evaluating aldoxorubicin for advanced soft tissue sarcomas and received 350 mg/m 2 (260 mg/m 2 doxorubicin equivalent) intravenously every 21 days, cumulative dose being 9100 mg/m 2 . Treatment was well tolerated, with manageable toxicities including alopecia, leukopenia, mucositis, and grade 3 neutropenia requiring G-CSF support. Notably, serial echocardiograms showed no evidence of cardiotoxicity, with a preserved ejection fraction (56–65%). He completed 26 cycles with stable disease, followed by a 7-month treatment break before receiving compassionate-use aldoxorubicin. Disease stability persisted for 6 months until progression, which was treated with radiotherapy. Three months later, systemic progression led to treatment discontinuation. This case illustrates the favourable cardiac safety profile of aldoxorubicin and efficacy in solitary fibrous tumours.